2022
DOI: 10.1038/s41559-022-01668-4
|View full text |Cite
|
Sign up to set email alerts
|

An earlier start of the thermal growing season enhances tree growth in cold humid areas but not in dry areas

Abstract: Climatic warming alters the onset, duration and cessation of the vegetative season. While prior studies have shown a tight link between thermal conditions and leaf phenology, less is known about the impacts of phenological changes on tree growth. Here, we assessed the relationships between the start of the thermal growing season (TSOS) and tree growth across the extratropical Northern Hemisphere using 3451 tree-ring chronologies and daily climatic data for 1948-2014. An earlier TSOS promoted growth in regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 74 publications
5
40
0
Order By: Relevance
“…As the "magnifying glass" of global climate change, the effects of T and P changes on vegetation coverage in the Qinghai-Tibet Plateau have been confirmed in many studies [54,55]. Previous studies have shown that climate warming may alter vegetation phenology, leading to an earlier vegetation growth season and promoting vegetation growth in high-latitude cold and wet areas [56]. However, we found that the increase in T of the QLB is limited, and the T _con to the growth in vegetation cover is not significant.…”
Section: The Impact Of Climate Change On Changes In Vegetation Covermentioning
confidence: 89%
“…As the "magnifying glass" of global climate change, the effects of T and P changes on vegetation coverage in the Qinghai-Tibet Plateau have been confirmed in many studies [54,55]. Previous studies have shown that climate warming may alter vegetation phenology, leading to an earlier vegetation growth season and promoting vegetation growth in high-latitude cold and wet areas [56]. However, we found that the increase in T of the QLB is limited, and the T _con to the growth in vegetation cover is not significant.…”
Section: The Impact Of Climate Change On Changes In Vegetation Covermentioning
confidence: 89%
“…Given that the Pan-Third Pole is projected to warm faster than the global average, the climate control of spring phenological changes might shift from temperature to precipitation over the Pan-Third Pole. Besides, the earlier start of the growing season may lead to enhanced vegetation growth ( Gao et al., 2022 ), but can increase water scarcity during the summer ( Lian et al., 2020 ). How the changes in spring phenology over Pan-Third Pole affect regional carbon and water flux still need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the 1.6ºC increment in the reconstructed data is in accordance with global modeled trends 1,33 , however our estimates correspond to a relatively cold region, which implies potentially that the boreal forest is warming at a faster-than-expected rate, as it has been observed in other boreal regions 2, [34][35][36][37] . Nonetheless, the fast season-specific AirTemp trends in the last 150 years, particularly in the spring (1.5ºC increment), is of great relevance and only recently studies have commenced assessing the impacts high spring AirTemp can have on boreal and other snow-covered forests 38,39 . Finally, similar AirTemp rises between the previous 30 and 150 years (1.5 vs 1.6ºC), show temperature rise has occurred in the last 30 years, and more specifically within the last decade.…”
Section: Historic Temperature Trends Water Balance and Tree Growthmentioning
confidence: 99%